Plexiform angiomyxoid myofibroblastic tumour of the duodenum: a rare entity. (27th July 2015) - Banerjee, Niladri; Gupta, Shahana; Dash, Suvashis; Ghosh, Shibajyoti
Abstract : Plexiform angiomyxoid myofibroblastic tumour (PAMT) has recently emerged as a new entity among gastrointestinal mesenchymal tumours. All of the 27 cases reported until now originated from the stomach. We report the first case of a duodenal PAMT arising from the first part of the duodenum in a 19-year-old woman presenting with upper abdominal pain and an abdominal lump.